Development of data acquisition system for dynamic analysis in ski jumping - Tsunoda, K.; Sasaki, T.; Hoshino, H.; Ichikawa, K. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: In the dynamics of ski jumping, it is necessary to measure the forces on the jumper. In the air, the jumper receives the gravity and aerodynamic force. Then the jumper produces rotational momentum. The angle of the jumper and the direction of motion change greatly. It is important to measure the body momentum during ski jumping. We developed a compact measurement device, combined accelerometer, and gyroscope. The purpose of this study is the development of an analysis system, including a measurement device, for ski jumping.